Influence of information support system on ICT use by distance learners in university of Lagos, Nigeria (2014)
The use of modern technology in Education is the key to an increased drive for learning which shape learners critical and analytic competencies with respect to disciplinary knowledge. Distance education (DE) is a system of learning driven by computer linked to internet. The flexible nature of DE avail students who are unable to attend full time education due to age, social or religious barriers. However, in Nigeria, the University of Lagos distance learning Institute has its shortfalls traced to poor student support system, which affects the service delivery to students. The study examined Influence of Information Support on ICT use by distance learners. Correlational survey was used in which Information Support System and ICT use was observed. The study population consists of representative students from faculty of Education, Business Administration and Social Sciences make up the study population. Multistage sampling was used with 3% of each population from eight departments, randomly selected to represent sample size of 255 respondents. The findings ranked high Administrative Support, Student Support System. Cybercafé is the most available internet access point to distance learners. The study concludes that Information support on ICT use have impact on distance learners in University of Lagos Nigeria.